Advancing Indigenous Research Sovereignty: Public Administration Trends and the Opportunity for Meaningful Conversations in Canadian Research Governance - Williams, Keith J.; Umangay, Umar; Brant, Suzanne (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
Federally funded research in Canada is of significant scope and scale. The implications of research in the colonial project has resulted in a fraught relationship between Indigenous Peoples and Western research. Research governance, as an aspect of public administration, is evolving. The relationality inherent in new public governance (NPG)—a nascent public governance regime—may align with Indigenous relationality concepts. Recent societal advances, such as the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP), the Truth and Reconcilliation Commission of Canada (TRC), and the Indigenous Institutes Act in Ontario, provide further impetus for Indigenous self-determination in multiple domains including research. This article advocates for Indigenous research sovereignty and concludes with suggestions for ways in which federal funding agencies, specifically the Social Sciences and Humanities Research Council (SSHRC), could contribute to the advancement of Indigenous research sovereignty.